Análisis de la demanda eléctrica en la empresa servicios industriales y petroleros servinpet para determinar la cargabilidad del sistema en las condiciones actuales con incorporación de la nueva carga - Bassantes Fernández, Darwin Patricio (2017)
The present project is oriented to the analysis of the electrical demand with the purpose of determining the degree of load ability of the transformer whose power is of 100 KVA, a general analysis of the company was realized by means of measurement element FLUKE 1735 network analyzer, obtaining characteristic measurements as voltage, current, power and power factor with which it is operating. The electrical parameters were evaluated, obtaining the comparative parameters with the current regulations, issued by the ARCONEL-CONELEC regulation 004/01 of quality of service. The interpretation of results was carried out in ETAP software 12.6.0 with results from critical zones, which allowed to propose technical solutions of the electrical system correcting existing faults. With the current simulation, the percentage of load capacity of the transformer is 31.4% now, with the implementation of the new load, this value increases to 38.8%, it is possible to indicate that the factor of utilization, demand, simultaneity ,it is less than 50%, since they are not constant charges....